Utilization of QGIS and Avenza Maps-Based Digital Maps in Geography Learning in High Schools - Aprianto Sabihi; Sunarti Suly Eraku; Nurfaika (International Journal of Technology and Education Research, 2025)
The role of learning media as a direct or indirect object for students cannot be ignored in the learning process. However, most teachers have not yet fully utilized geographic information system technology as a learning resource or representative media for learning in schools. Therefore, it is necessary to utilize GIS technology in the development of digital map media integrated with QGIS software and the Avenza Maps application in learning materials on the basics of mapping. The general objective of this study is to utilize digital map media based on QGIS and Avenza Maps to improvespatial thinkingstudents. The method used is research and development or Research and Development using the ADDIE development model. Based on a limited trial of the effectiveness of the media at SMA Negeri 2 Gorontalo, it shows that there are 34 students who were tested who achieved a mastery score of 31 students, while in a wider trial at several high schools the results showed that digital map media is very good for use in schools in the learning process. This is evidenced by student mastery data in evaluating the learning process with a presentation value between 80-100%. The presentation results are included in the category (Very Good) thus digital map media based on QGIS and Avenza maps are very good for use in the learning process.